WEED FLORA DISTRIBUTION AND ITS ETHINOBIOLOGICAL VALUE IN RAINFED RICE ECOSYSTEM UNDER MID HILL SITUATION - MUKHERJEE, DHIMAN (Annals of Agricultural Research, 2014)
A survey on weed flora and their distribution pattern in the Kalimpong and its adjoining rice growing area had been observed over a period of three years (2006-2008) in kharif season. Detail studies on the life cycle, mode of propagation, nature of stem, leaf structure and economic value of the most common weeds species have been seen. Forty eight weed spp. Were identified belonging to 28 families in this region which comprised of 62% if the total weed population. A number of weeds have the medical vlue of great importance. Regarding family-wise contribution Poaceae contributing highest number (9) in hill which are useful for food and fodder purpose followed by Cyperaceae (4), Amaranthaceae (3), Commelinaceae (3) and Euphorbiaceae (3). Most of the weeds were propagated by seeds and few of them by vegetative means. Ethenobiological studies revealed that, these weeds were very helpful for various medical treatments. Local peoples particularly Lepcha, Bhutia and Tibetans used this weed herb as folk medicine for various disease.